Humanización de los procesos de servicios de salud en personas discapacitadas (2016)
It is important to give to know that according to the State, recognizes in our constitution the dignity that belongs people with limitations in their fundamental, economic, social and cultural rights for their fulfillment and community inclusion rights. In this sense, it will establish the design, production and dissemination of specialized educational materials that support the therapeutic process for this population It will determine whether health services a represented in a timely and comprehensive way to population with disabilities present in the St. Alexander Foundation located in Tunja city, where the basic elements that determine the presentation of rehabilitation services and other processes will be analyzed within the same Institution, as the State have to ensure adequate supply of these products (social security) and to supports cientific technological level, being a vulnerable population.Through surveys and a close observation, it will analyze if the institution use the aids mentioned before and if these children receive psychological, therapeutic, occupational support according to their needs and establish if their family circle also participates actively in their process of adaptation and community out reach to supply their quality of life.It will take a simple population at random according to pathologies to establish the disability, handicap and difference manifests grade. Subsequently, it will identified the causes and if the treatment was received or not.